The search for a socialist El Dorado : Finnish immigration to Soviet Karelia from the United States and Canada to in the 1930s - Golubev, Alexey; Takala, Irina (East Lansing : Michigan State University Press, 2014)
Drawing on a vast range of new sources, including their own oral history interviews, Golubev and Takala have written the first major account in English of a most dramatic and revealing, yet still little-known, episode in twentieth-century history--the mass immigration of North American Finns to Soviet Karelia in the 1930s. Meticulously researched this volume offers powerful and moving insights into not only the causes and course of the immigration but also into the experiences of the migrants and the tragic fate that awaited many of them during the Stalinist repressions.
Finnish immigrants in North America and Russia -- Two perspectives on Soviet immigration policy : Moscow and Petrozavodsk -- To Karelia! -- The failure of the immigration program -- American and Canadian immigrants in Soviet economy -- North American Finns in Soviet culture -- Challenges of cross-cultural communication -- American and Canadian Finns in the great terror -- Wartime and after.
Julkaistu myös verkkoaineistona.
Sisältää bibliografisia viitteitä ja hakemiston.
Keywords: Finnish Americans -- Russia (Federation) -- Karelia -- History -- 20th century; Finns -- Russia (Federation) -- Karelia -- History -- 20th century; amerikafinländare; amerikansuomalaiset; erfarenhetsberättelse; finländare i Kanada; förtryck; kanadansuomalaiset; migranter; migration (människor); muistitieto; siirtolaiset; siirtolaisuus; sorto; Canada -- Emigration and immigration -- History -- 20th century; Karelia (Russia) -- Emigration and immigration -- History -- 20th century; Soviet Union -- History -- 1925-1953.; United States -- Emigration and immigration -- History -- 20th century; Förenta staterna; Kanada; Kanada; Karelen; Karjala; Neuvosto-Karjala.; Neuvostoliitto; Sovjet-Karelen.; Sovjetunionen; Yhdysvallat; 1930-luku.; 1930-talet.